Enhancing Nitrogen Use Efficiency, Growth, and Biomass Yield of Pak Choy on Coastal Entisols with a Combination of Reduced Nitrogen Fertilizer and Zeolite-Based Slow-Release Fertilizer - Resti , Cynthia; Handajaningsih, Merakati; Marwanto (Badan Penerbitan Fakultas Pertanian (BPFP), Fakultas Pertanian, Universitas Bengkkulu, 2024)
Coastal sandy soil has a low capacity to hold water and nutrients, trigerring high doses of fertilizer application. Therefore, this study aims to determine the optimal mixture of urea and zeolite-based slow-release fertilizers (SRF) that can reduce application of inorganic fertilizer while improving nitrogen use efficiency (NUE), growth dynamics, and yield of pak choy cultivated on coastal Entisols. This research was conducted from October to December 2023 in the Plant and Soil Research field on the outskirts of the Bengkulu University campus. The treatments used were a combination of urea and SRF, consisting of 0% N-Urea, 100% N-Urea, 75% N-Urea + 25% N-SRF, 50% N-Urea + 50% N-SRF, 25% N-Urea + 75% N-SRF, and 100% N-SRF. The study was set up in a completely randomized design with five replications. The results demonstrated that the treatments enhanced the growth and biomass yield of pak choy, as well as NUE. The combination of 50% N-Urea + 50% N-SRF (equal to 200 kg urea ha-1 + 608.5 kg SRF ha-1) resulted in higher leaf area, fresh shoot weight, dry shoot weight, fresh plant weight, N- uptake, and NUE compared with the application of 100% N-Urea (400 kg urea ha-1). The NUE for the combination of 50% N-Urea + 50% N-SRF was 36.36%, which was 13.63% compared to 100% N-Urea with an NUE of 34.09%. Therefore, using this SRF allows for a reduction in urea requirements by up to 50%.NUE and nitrogen uptake show a very high positive association (r=0.941, p<0.01). Keywords: activated zeolite matrix, , coastal sandy soil, inorganic nitrogen fertilizer, slow- release fertilizer